Period poverty, reuse needs, and depressive symptoms among refugee menstruators in Jordan's camps: a cross-sectional study - Nadia Muhaidat; Joud Al Karmi; Abdulrahman M. Karam; Farah Abushaikha; Mohammad Ali Alshrouf (BMC, 2024)
Abstract Background Period poverty is a significant issue that impacts the physical and psychological well-being of menstruators worldwide which can further contribute to poor mental health outcomes. For menstruators living in refugee camps, access to menstrual hygiene products is often limited or non-existent, leading to increased anxiety, shame, and embarrassment. Therefore, this study aimed to assess the prevalence of the period poverty and to comprehensively analyze the association between period poverty, reusing menstrual products, and depressive symptoms among menstruators living in refugee camps in Jordan. Methods A cross-sectional study surveyed refugee menstruators living in camps in Jordan, aged post-menarche to pre-menopause. Data collection included socio-demographics, menstrual practices, and depressive symptoms using the Patient Health Questionnaire (PHQ-9). Period poverty was assessed through affordability and frequency of struggles with menstrual products. Chi-squared test, independent sample t-test, One Way Analysis of variance (ANOVA) followed by Post hoc, and logistic regression models were used in the analysis. Results The study included a diverse sample of 386 refugee menstruators living in camps in Jordan (mean age 32.43 ± 9.95, age range 13-55). Period poverty was highly prevalent, with 42.0% reporting monthly struggles to afford menstrual products, and 71.5% reusing menstrual products. Univariate analysis revealed that experiencing period poverty was significantly associated with a younger age of marriage, increased number of children, lower education level, lower mother and father education levels, unemployment, decreased monthly income, absence of health insurance, lower reuse need score, and increased PHQ-9 score (p < 0.05). Menstruators experiencing monthly period poverty were 2.224 times more likely to report moderate to severe depression compared to those without period poverty (95% CI 1.069-4.631, P = 0.033). Conclusion This study highlights a significant association between period poverty and depressive symptoms among refugee menstruators in living in camps in Jordan, as high rates of period poverty were associated with a 2.2-fold increased likelihood of reporting moderate to severe depression. Addressing period poverty in refugee settings is crucial for mitigating depression risks and enhancing overall well-being.